Designing robot behavior in human-robot interactions - Liu, Changliu, 1990-; Tang, Te; Lin, Hsien-Chung; Tomizuka, M. (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
"In this book, we have set up a unified analytical framework for various human-robot systems, which involve peer-peer interactions (either space-sharing or time-sharing) or hierarchical interactions. A methodology in designing the robot behavior through control, planning, decision and learning is proposed. In particular, the following topics are discussed in-depth: safety in the process of during human-robot interactions, efficiency in real-time robot motion planning, imitation of human behaviors from demonstration, dexterity of robots to adapt to different environments and tasks, cooperation among robots and humans with conflict resolution. These methods are applied in various scenarios, such as human-robot collaborative assembly, robot skill learning from human demonstration, interaction between autonomous and human-driven vehicles, etc"--
"A science publishers book."
OCLC-licensed vendor bibliographic record.
Keywords: Human-robot interaction; Robotics; COMPUTERS / Machine Theory; COMPUTERS / Computer Engineering; SCIENCE / Life Sciences / General